2017
DOI: 10.1055/s-0043-111888
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an e-learning system for diagnosis of gastric lesions using magnifying narrow-band imaging: a multicenter randomized controlled study

Abstract: Magnifying narrow-band imaging (M-NBI) is useful for the accurate diagnosis of early gastric cancer (EGC). However, acquiring skill at M-NBI diagnosis takes substantial effort. An Internet-based e-learning system to teach endoscopic diagnosis of EGC using M-NBI has been developed. This study evaluated its effectiveness. This study was designed as a multicenter randomized controlled trial. We recruited endoscopists as participants from all over Japan. After completing Test 1, which consisted of M-NBI images of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 25 publications
(24 reference statements)
0
41
1
Order By: Relevance
“…The range of confidence intervals was calculated based on the results of each participant. The multivariable logistic regression analysis of factors that contributed to an increase of ≥10% in the accuracy was conducted based on classification of endoscopists (non‐beginners or beginners), sex (male or female), total number of endoscopies conducted, number of endoscopies conducted in the last year, pretest score (30 points at maximum), and number of views of the educational video 15. In the logistic regression analysis, regression coefficients (β) were also calculated to facilitate comparison of each factor.…”
Section: Methodsmentioning
confidence: 99%
“…The range of confidence intervals was calculated based on the results of each participant. The multivariable logistic regression analysis of factors that contributed to an increase of ≥10% in the accuracy was conducted based on classification of endoscopists (non‐beginners or beginners), sex (male or female), total number of endoscopies conducted, number of endoscopies conducted in the last year, pretest score (30 points at maximum), and number of views of the educational video 15. In the logistic regression analysis, regression coefficients (β) were also calculated to facilitate comparison of each factor.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple online training courses have however been developed. Two image-based studies demonstrated the efficacy of dedicated online training courses in improving practitioners' abilities to distinguish between gastric cancer and non-cancer using magnifying NBI with the validated VS classification [49,50]. Another study with high definition NBI videos showed a 10 % increase in global accuracy after an online training course on a simplified NBI classification [52].…”
Section: B Training/learning Steps For Optical Diagnosismentioning
confidence: 99%
“…In upper gastrointestinal (GI) endoscopy, learning curves of VC are investigated in various settings, such as the assessment of BE and esophageal and gastric lesions. [13][14][15][16][17][18][19][20] One study investigated the learning curve of BE assessment using magnified NBI (M-NBI) in endoscopists with-and without previous M-NBI experience. 15 Before the onset of the study, the participants underwent a structured learning program and received histological feedback after every assessed video.…”
Section: Implications For Patient Carementioning
confidence: 99%